EVALUASI STRATEGI DAN IMPLEMENTASI PENGELOLAAN SISTEM LAYANAN ELEKTRONIK DI INSTANSI PEMERINTAH DENGAN MENGGUNAKAN FRAMEWORK DARI INFORMATION TECHNOLOGY INFRASTRUCTURE LIBRARY VERSI 2 (Studi Kasus Sistem Teknologi Informasi Di Pemerintah Kota Yogyakarta) - , Sami Kandha Dipura; , Ir. Surjono, M.Phil. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aimed to measure the effectiveness of e-service system management in the municipal government of Yogyakarta. The measured field had two areas, the area of strategy, and the area of implementation, because these two areas must be present in any IT system management (ITSM). Both concepts of strategy and implementation was aligned with the ITIL framework Version 2, ITIL framework could be used as a standard evaluation for IT system in government agencies, the formulation of the problem in this study was how to measure the level of e-service effectiveness in the area of strategy and in the area of implementation which were governed by municipal government of Yogyakarta. The study was held in three months from 20 September until 20 November 2013. The method which was used in this research was descriptive-evaluative, with qualitative approach and deductive reasoning. The sampling method used was non-probability sampling technique with some judgements. Representative sample of the population of the authorities for the system management of electronic services in the municipal city of Yogyakarta was TIT (Telematics and Information Technology) Department, itâs a special agency which was responsible for the success of e-Government in the municipal Government of Yogyakarta. After an examining by the analysis in which the research was conducted, it could be concluded that in the municipal Government of Yogyakarta based on framework ITIL Version 2 the area of strategy was less effective (the value was 67.83 %), and for the scope of service delivery as part of the area of implementation in information technology system which was applied also less effective (the value was 67.17 %), also something similar to the scope of the service support as part of the implementation area of information technology system management which was applied also less effective (the value was 63.03